Síntese de derivados benzimidazólicos contendo grupos benzamidas e N'-ilideno-substituído-benzoidrazidas ligados na posição-2' do benzimidazol como novos potenciais agentes antitumorais - Tanabe, Eduardo (2012)
Based on studies of antitumor activity performed by our research group using the β-carboline nucleus, we synthesized a series benzimidazole of derivatives bearing the same substituents of β-carboline derivatives which showed the best pharmacological activity. As the β-carbolines, the benzimidazole presents itself as a good pharmacophoric group, being widely used in medicinal chemistry. The synthesized derivatives containing benzamide group (28a-g) and (E, Z)-N -ylidene-substituted benzohydrazide group (32a-f e 33a-e) in the position2 of the benzimidazole showed poor antitumor activity against glioma cells (U251), breast cancer (MCF-7), ovarian expressing phenotype multiple drugs resistance (NCI-ADR/RES), renal carcinoma (786-0), lung (NCI-H460), human ovarian carcinoma (OVCAR-03) colon (HT-29) and leukemia (K562), with the exception of the derivatives N -(o-chloro-benzylidene)-2-(1 H-benzimidazol -2 yl) benzohydrazide (32c) and N -(o-chlorobenzylidene)-2-(6 -methyl-1 Hbenzimidazol-2 -yl)benzohydrazide (33c), in which both showed IC50 values lower than 10.0 µM for almost all tumor cell lines. Nevertheless, it was possible to draw some conclusions that will help our group to guide the future researches regarding the use of the benzimidazole nucleus in the search for new antitumor agents.